The research on the selection of the rice transfer machine. (2019) - Yang, Xin; Zeng, Zhenxiang; Wei, Jinyu; Cai, Xinjiang
This article sets the fuel consumption index and the working efficiency index as the main basis for the rice transfer machine. Through the simulation experiment of different load transfer machine models, it reaches their fuel law in the rice field. Finally it determines the best model by the optimal ratio and the working efficiency, which extremely satisfies the requirement of the short payback period and the long service life. The transfer machine reduces the labour intensity of the future agriculture field, improves the production efficiency and reduces the labour cost. And it also has an important role in improving business efficiency.